2015
DOI: 10.1109/tifs.2015.2405345
|View full text |Cite
|
Sign up to set email alerts
|

Attack of Mechanical Replicas: Liveness Detection With Eye Movements

Abstract: This paper investigates liveness detection techniques in the area of eye movement biometrics. We investigate a specific scenario, in which an impostor constructs an artificial replica of the human eye. Two attack scenarios are considered: 1) the impostor does not have access to the biometric templates representing authentic users, and instead utilizes average anatomical values from the relevant literature and 2) the impostor gains access to the complete biometric database, and is able to employ exact anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Firstly, the adversary is likely to be solving a harder problem than the system; while the system needs to build a discriminative model that allows making a binary decision about user's identity, the adversary needs to actually generate eye movements which correspond to the legitimate user. An indication of the difficulty of artificially creating eye-movements can be found in work by Komogortsev et al [28], which evaluated the complexity of a significantly simpler problem: artificially generating 1-dimensional eye movements. The paper showed that those movements could be distinguished from natural recordings with high accuracy; creating realistic 2D eye-movements that correspond to a specific user is likely to be significantly harder.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the adversary is likely to be solving a harder problem than the system; while the system needs to build a discriminative model that allows making a binary decision about user's identity, the adversary needs to actually generate eye movements which correspond to the legitimate user. An indication of the difficulty of artificially creating eye-movements can be found in work by Komogortsev et al [28], which evaluated the complexity of a significantly simpler problem: artificially generating 1-dimensional eye movements. The paper showed that those movements could be distinguished from natural recordings with high accuracy; creating realistic 2D eye-movements that correspond to a specific user is likely to be significantly harder.…”
Section: Discussionmentioning
confidence: 99%
“…Oleg el al. [18] proposed Liveness detection techniques in the area of eye movement biometrics. Two attack scenarios were considered, in which the imposter does and does not have direct access to the biometric database.…”
Section: Iris Anti-spoofingmentioning
confidence: 99%
“…For example, soft biometric traits extracted by the eye movements can provide advanced antispoofing resistance [23,24] and facilitate tasks like continuous authentication [25]. Other advantages of eye movement biometrics are the provided ability for touch-less (remote) capturing, and the potential employment of the extracted features for medical monitoring purposes [26,27].…”
Section: Introductionmentioning
confidence: 99%